Effect of adding daytime Class III Elastics to the alternate rapid maxillary expansion-constriction and reverse headgear therapy - A randomized clinical trial - Jean James; Shobha Sundareswaran; Shijo Davis (Wolters Kluwer Medknow Publications, 2020)
OBJECTIVE: To evaluate the skeletal, dental and soft tissue cephalometric changes by addition of daytime Class III elastics to the Alternate Rapid Maxillary Expansion-Constriction (AltRAMEC) and Reverse Headgear (RH) protocol in skeletal Class III patients with maxillary retrusion. Material and Methods: 54 patients with maxillary retrusion and CVMI (Cervical vertebral maturity index) <CS3 were randomly allocated to an AltRAMEC/RH group (group 1) and AltRAMEC/RH/Class III elastics group (group 2). Each group underwent 5 weeks of AltRAMEC using bonded RME (Rapid Maxillary Expansion) appliance, followed by reverse headgear therapy with a Petit type facemask for 4-5 months. The protraction so obtained was maintained by the use of daytime Class III elastics in group 2. A total of twenty skeletal, dental and soft tissue parameters were evaluated by a blinded examiner. Results were evaluated statistically. Results: Significant forward movement of the maxilla with counter-clockwise rotation, improved intermaxillary relationships, downward and backward movement of the mandible, and favourable soft tissue changes were observed in both the groups under study. The results were more pronounced in group 2. Increase in vertical dimensions, proclination of maxillary and retroclination of mandibular incisors was also observed. Statistically significant differences were present between the two groups for all of the maxillary and mandibular skeletal, intermaxillary and two of the soft tissue parameters tested; while the differences were not found to be significant for dental parameters. Conclusion: Addition of Class III elastics to the AltRAMEC/RH protocol yielded more pronounced, favourable and statistically significant results.